المدرسة الجزائرية ودورها في تنمية الجانب المهني لدى التلميذ - سالمي, مسعودة (جامعة الوادي - University of Eloued, 2022)
تهدف الدراسة الحالية إلى التعرف على كيفية تنمية الجانب المهني للتلاميذ داخل المدرسة الجزائرية وذلك بالتعرف على الارشاد والتوجيه المدرسي المهني الممارس في المراحل التعليمية الثلاثة المرحلة الابتدائية والمرحلة المتوسطة والمرحلة الثانوية وذلك من اجل تضييق الفجوة بين مخرجات ومتطلبات سوق العمل. فالدراسة تتحدث اولا حول المدرسة ووظائفها بشكل عام، وتسلط الضوء على المدرسة الجزائرية بمراحلها الثلاث الابتدائي والمتوسط والثانوي. ثم تتطرق الى التوجيه المدرسي والمهني في المدارس. The current study aims to identify how to develop the professional aspect of students within the Algerian school by identifying the vocational school guidance and guidance practiced in the three educational stages, the primary stage, the intermediate stage, and the secondary stage, in order to narrow the gap between the outputs and requirements of the labor market. The study first talks about the school and its functions in general, and sheds light on the Algerian school in its three stages, primary, intermediate and secondary. Then it deals with school and vocational guidance in schools.
The Algerian school and its role in developing the student's professional side
مقال
Keywords: المدرسة الجزائرية ، التوجيه المهني; Algerian School, Career Guidance